Effect of particle size on color and NIR reflectivity of (Fe,Cr)2O3 black pigment - Toy, Emre; Aslan, Emre; Yesilci, Emine; Karaahmet, Oguz; Grijalbo, Alejandro; Cicek, Bugra (ELSEVIER, 2025)
Pigments play a critical role in imparting color and functional properties to various materials. Carbon black effectively provides high color strength and a deep black color to materials. However, its use is restricted in NIR sorting systems for recycling due to its absorption of electromagnetic waves necessary for sorting of plastics. Moreover, when used in surface coatings, this pigment absorbs solar energy, leading to an increase in the surface temperatures, contributing to global warming. To eliminate these limitations, NIR reflective inorganic black pigments were synthesized with metal oxides. In this study, (Fe,Cr)2O3 black pigments were prepared through the solid-state reaction of a metal oxide mixture at 1100 degrees C. The pigments were milled from micron-sized particles to nano-sized particles (Dv90 = 1, 5, 10 mu m). Color measurements in CIE L*a*b* were conducted on two different applications: plastic/masterbatch and paint/film. The L*, a* and b* values of pigments increased by decreasing of particle size which made it lighter, redder and yellower. On the other hand, the color strength of the pigments were increasing by milling. The UV-VIS-NIR spectrophotometer was utilized to measure the powder's reflectance in the 200-2500 nm wavelength range. (Fe,Cr)2O3 black pigments with different particle sizes exhibit similar RNIR, approximately 65 %. These properties make them suitable for recycling plastic materials by enabling sorting through NIR technology. Additionally, due to their NIR reflectance, they fall into the Cool pigment category, reflecting a significant portion of sunlight unlike carbon black (0.7 %). The pigment's inorganic structure makes it environmentally friendly for sustainable pigment applications.
Keywords: Pigment; Particle size; NIR; Recycling; Cool; REFLECTANCE SPECTRA; OPTICAL-PROPERTIES; SOLAR REFLECTANCE; CRYSTAL-STRUCTURE; TEMPERATURE; PERFORMANCE; MORPHOLOGY; STRENGTH; SPINEL; OXIDES; Chemistry